A Narrative Local Wisdom-Based Educational Model for Developing Human Capital and Social Capital to Strengthen Defense in the Kalimantan Border Region - Gregorius Henu Basworo; Ryan Teo (Yayasan Adra Karima Hubbi, 2026)
Background. Defending the nation inherently entails fostering community resilience, and the national security architecture requires local stability to serve as the first firewall of defense. Education in border regions must be regarded as a strategic instrument capable of developing human capital and social capital in an integrated manner, with local wisdom as its primary foundation. Purpose. This conceptual study aims to formulate a local wisdom-based educational model that integratively develops human capital and social capital in order to reinforce community defense capacity in the Kalimantan border region. Methods. A systematic literature synthesis was conducted using nationally accredited journals (SINTA 2 and above), Scopus-indexed international journals, scholarly books, and official government documents published between 2020 and 2026. From 86 initially gathered works, 52 core texts were selected based on relevance to the integration of human capital, social capital, and local wisdom within border education and defense. Data were analyzed using qualitative content analysis through repeated reading, coding, thematic grouping, and analysis of inter-theme relationships. Results and Discussion. The synthesis revealed three main intertwined themes: human capital development through border education (knowledge, skills, character), strengthening social capital as a community resilience network (bonding, bridging, linking), and Kalimantan's local wisdom (huma betang, gotong royong, musyawarah adat) as the pedagogical-ideological foundation. Conclusion. The proposed model provides a theoretical basis for further empirical testing and practical guidance for local governments, the Indonesian National Armed Forces (TNI), and customary institutions in designing culturally grounded educational programs for border areas.